Fuzzy expert system for beach volleyball fundamentals evaluation - Noal, R. B. (Lecturas: Educación Física y Deportes, 2005)
This paper proposes an evaluation of the beach volleyball fundamentals using the fuzzy theory concepts. The model is composed by three evaluation groups: the first one makes the evaluation of the offensive fundamentals, the second one makes the evaluation of the defensive fundamentals, and the third unifies the obtained results. This division permits a visualization of the fundamentals in a clearer way. The proposed model implementation and test results of volleyball matches are also presented.